Kinematic analysis of rugby lineout throws in the Six Nations Tournament - Martin, I.; Mira, P.; Salinas, J. M.; Vaz, L.; Carreras, D. (Revista Internacional de Ciencias del Deporte, 2018)
This study examines 126 successful, six- or seven-man lineouts of the 2013 Six Nations Tournament. Data were extracted from footage of the competition to calculate kinematic variables along with jumper position. Through cluster analysis, six types of throw were identified according to distance and velocity: short-fast, short-slow, medium short-fast, medium short-slow, medium long and long. Significant differences were detected in all the variables examined depending on the throw category (throw distance P<0.001; Partial eta square 2=0.932, height P=0.032; 2=0.096, flight time P<0.001; 2=0.789, starting angle P<0.001; 2=0.502, initial velocity P<0.001; 2=0.767 and jumper position P<0.001; 2=0.641). In the discriminant analysis, all variables except jumper position were able to correctly classify 100% of the throws. In addition, we differentiated the six participating teams, finding significant differences in throw height (Scotland vs England difference means d=0.32m, Ireland d=0.36m or France d=0.37m), flight time (Italy vs England d=0.34s or Ireland d=0.33s) and angle (Italy vs England d=9.72º or Ireland d=8.49º and Scotland vs England d=8.27º or Ireland d=7.04º). Our findings have implications for training and team analysis (own and rival) and also provide direction for future investigations.